Repercussão geral e súmula vinculante em matéria tributária - Mrad, Ricardo (2010)
The present work has as an aim to analyze the general repercussion institutes and the entailed emulate and to apply them for some tributary law practical cases. With this purpose, some methodological premises were draught, as the law conception as a communicational system. Not-withstanding the distinction between the positive law system and the system of the Law Science were accepted and applied, glimming the existence of the communication between both, the referred system which can constitute in another communicational system, called judiciary system. Furthermore, the communicational theory proposed by Luhmann was analyzed and it was concluded that what passes in human consciousness it is found outside the communicational plan, and, according to the Luhmann teachings, the judicial rule is set in the understanding act, which is enunciated by a law applicant. In a second moment, it was emphasized the difference between the two western judiciary systems (common and civil) and demonstrated that the same were becoming much closer. In this stage, it was focused the system of incidental control and diffused of the constitutionality of the normative acts, and it was also developed in the common law and the concentrated system, which was developed in the civil law. After, it was identified that Brazil, the country of the civil law, adopted a typical system of the constitutionality control of the common law countries. This fact caused the inefficiency of the system, which gradually evolved during the 20th century until it reaches the present time, hybrid. Also, it was demonstrated that in Brazil, the free conviction of the judge in being the general rule is increasing the rules numbers that check the most various judicial decisions and extra proceeding relevant efficacy to the other process solutions, reaching, in certain cases draught constitutionally, including the entail. Following, it was analyzed the theme of general repercussion, in its constitutional and infra constitutional meaning and the entailed emulate, aiming to demonstrate its particularities and the principal functions, mainly what concerns the tasks of unifying the jurisprudence, rationalizing and checking the efficacy to the work which is developed by Supremo Tribunal Federal . Finally, some tributary law cases were analyzed under all the knowledge and tools that were developed during this study, which does not have the purpose the construction of the theories, but it was aimed how these theories are created, developed and discarded. Then, this study was focused at demonstrating how the dynamics of the judicial system works, aiming the understanding of the existent coordination between the doctrine and the law professionals